MYCOTECHNOLOGICAL PRODUCTION OF LACCASE BY PLEUROTUS OSTREATUS-P1 AND ITS INHIBITION STUDY - A. Nadeem; S. Baig; N. Sheikh3 (Journal of Animal and Plant Sciences, 2014)
Laccase is one such copper protein belonging to the oxidoreductase family that oxidizes a large array of organic substrates i.e phenolic and non-phenolic compounds.An attempt was made to screen Pleurotus ostreatus-P1by plate testonKirk medium for laccase production by using guaiacol and syringaldazine as indicators and six different liquid culture media having varied composition were work out for laccase production. Hyper Laccase production (5.5±0.33unit/ml) objective was achieved in medium 09-CBZ6 in combination with promising protein production (3mg/ml) under optimized fermentation conditions (pH: 5.5; Temperature: 30°C; Time: 7th day). Laccase production by a long way intensified by the adding of glucose (1.5%, C/N:15) and inducer (CuSO4) gave promising results (13.72±0.30U/ml) and other inducers followed laccase production as Na2SO4> ZnSO4> FeSO4> CaCl2. Sodium Azide was found a significant inhibitor (100%) for laccase activity than SDS (87%) and EDTA (83%). Study brings to a close potential of Pleurotus ostreatus-P1for laccase production under optimized conditions for industrial applications.
Keywords: Laccase; Pleurotus ostreatus-P1; Kinetics; Inhibition; Culture Media